Massive hemorrhage after inspection bronchoscopy for carcinoid tumor. (2018) - Ayache, Mirna; Donatelli, Christopher; Roncin, Kara; AnsariGilani, Kianoush; Yang, Michael; Faress, Jihane; Teba, Catalina
Abstract: Carcinoid tumor is a neuroendocrine tumor that can arise in the bronchial tree and can be hypervascular. Here we describe a case of bronchial carcinoid tumor in a 34-year-old previously healthy male who presented with hemoptysis and right lung mass. Inspection bronchoscopy revealed bronchus intermedius endobronchial lesion and was complicated by urgent intubation and placement of endobronchial blocker for massive hemorrhage. Subsequent angiography with embolization of the bronchial artery supplying the mass resulted in control of bleeding. While massive hemorrhage has been described with biopsy of bronchial carcinoid tumor, this case suggests that careful planning for inspection bronchoscopy is needed when carcinoid tumor is suspected.